The repercussions of the Corona pandemic on the global oil market - Oukil, Hamida; Khomidja, Fatiha (Dirassat Journal Economic Issue, 2021)
The study aims to highlight the major impacts of the Corona pandemic on key variables of the global oil market as well as market players, as well as future expectations and future oil price scenarios. The study concluded that the impact of the pandemic on the mainly oil market variables in oil supply, demand and price in 2020 was significant, peaking in the second quarter, and with the adoption of and commitment to implement the crisis, the market is expected to recover in early 2021 and this recovery will continue until 2022. The study aims to highlight the major impacts of the Corona pandemic on key variables of the global oil market as well as market players, as well as future expectations and future oil price scenarios. The study concluded that the impact of the pandemic on the mainly oil market variables in oil supply, demand and price in 2020 was significant, peaking in the second quarter, and with the adoption of and commitment to implement the crisis, the market is expected to recover in early 2021 and this recovery will continue until 2022.